Preparation and characterization of carrageenan-embedded lanthanum iron oxide nanocomposite for efficient removal of arsenite ions from water. Issue 4 (13th January 2022) - Mudhulkar, Raju; Damarla, Krishnaiah; Pappula, Venkata Narayana
Abstract : Fabrication of lanthanum iron oxide nanosurface by a natural polysaccharide, carrageenan to develop nanocomposite useful for the removal of As 3+ from water. Eco-friendly, easily separable, low cost CA-LaFeNPs could efficiently remove As 3+ . Abstract : Arsenic (As) contamination in drinking water has grown into a global concern in recent years, which demands the development of various As remediation approaches. In this study, a new magnetic nanocomposite, carrageenan-embedded LaFeO3 nanoparticles (abbreviated as CA-LaFeNPs) was synthesized by a sol–gel process and used to remove arsenite [As(iii )] from water. The synthesized magnetic adsorbent was characterized by powder XRD, SEM, FTIR, VSM, and TGA. The adsorbent gel, CA-LaFeNP was mainly with LaFeO3 in nanoscale particles with a saturation magnetization of 13.33 emu g −1 and could be easily separated from water with a simple hand-held magnet in 2 minutes. The adsorption outcomes of the CA-LaFeNPs could be finely interpreted by Langmuir, Freundlich, and Tempkin isotherm models. The Langmuir isotherm model appears to have good regression coefficients, and maximum adsorption capacity was estimated to be 91 mg g −1 for CA-LaFeNPs at 27 °C and pH 7. The removal efficiency observed for CA-FeNPs was 91% up to the As(iii ) concentration of 700 mg L −1, while it decreased to 85% when the As(iii ) concentration was above 1200 mg L −1 . This low-cost and environmentally-friendly magnetic nanocomposite, CA-LaFeNPs could be more appropriate for real-world applications and also a substitute for the traditional magnetic nanoparticles.